2017
DOI: 10.1091/mbc.e16-04-0262
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 but not ROCK2 contributes to RhoA signaling and NMIIA-mediated contractility at the epithelial zonula adherens

Abstract: ROCK1 is the prominent isoform responsible for molecular organization of epithelial zonula adherens (ZA) and its contractile properties. ROCK1 selectively localizes NMIIA to ZA and supports cortical tension and GTP-Rho at the ZA. NMIIA, in a feedback loop, promotes cortical localization of ROCK1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Indeed, its loss leads to a lesscompact cortical actin rim and low cell-cell tension, while its overactivation upon ROCK2 loss generates more ventral stress fibers and increased cell-cell tension. This is in good agreement with its higher capacity than ROCK2 to phosphorylate myosin II light chain (Newell-Litwa et al, 2015;Yoneda et al, 2005) and its reported role on junctional tension in epithelial cells (Priya et al, 2017).…”
Section: Rock1 and Rock2 Are Both Required To Organize The Actomyosinsupporting
confidence: 90%
“…Indeed, its loss leads to a lesscompact cortical actin rim and low cell-cell tension, while its overactivation upon ROCK2 loss generates more ventral stress fibers and increased cell-cell tension. This is in good agreement with its higher capacity than ROCK2 to phosphorylate myosin II light chain (Newell-Litwa et al, 2015;Yoneda et al, 2005) and its reported role on junctional tension in epithelial cells (Priya et al, 2017).…”
Section: Rock1 and Rock2 Are Both Required To Organize The Actomyosinsupporting
confidence: 90%
“…, 2015 ). Moreover, ROCK1 knockdown in MCF-7 cells specifically reduced p-RLC localization to adherens junctions suggesting that ROCK1 preferentially regulates contractility in adherens junctions ( Priya et al. , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Myosin IIA functions as a scaffold that promotes RhoA-GTP output at junctions; Myosin IIA scaffolds ROCK1 at the ZA, and ROCK1 works through Rnd3 to prevent the accumulation of the Rho GAP p190RhoGAP-B, which would negatively regulate RhoA signaling at the ZA (Priya et al, 2015; Priya et al, 2017). Additionally, Myosin II filaments can serve as an F-actin bundling proteins.…”
Section: Junctional Roles For Myosin IImentioning
confidence: 99%